Effects of Levetiracetam on pilocarpine-induced seizures in mice - Aline de Albuquerque Oliveira (2005)
Levetiracetam (LEV) is a new antiepileptic drug effective as adjunctive therapy for partial seizures and in experimental models of seizures, including pilocarpine-induced seizures in rodents. Objectifying to clarify if anticonvulsant activity of LEV occurs near cholinergic muscarinic alterations, adult male mice received LEV injections before muscarinic agonistsâ administration. Pretreatment with LEV (30, 50, 100 or 200 mg/Kg, i.p.) increased the latency of seizures, latency of status epilepticus and latency of death on the seizure model induced by pilocarpine, 400 mg/Kg, s.c. (P400). LEV (200 mg/Kg, i.p., LEV200) pretreatment abolished seizures in 53% (20/38) of the animals; reduced status epilepticus appearance in 58% (22/38); increased deathâs latency in 116% compared to P400 group; protected 61% (23/38) of the animals from death and also reduced the intensity of tremors induced by oxotremorine (0,5 mg/kg, i.p). [3H]-N-methylscopolamine binding assays in mice hippocampus showed that LEV200 pretreatment reverts the downregulation on muscarinic acetylcholine receptors (mAChR), induced by P400 administration, bringing back these density values to control ones (0,9% NaCl, i.p.). However, subtype-specific binding assays revealed that P400 and LEV200 alone treatments results in M1 and M2 subtypes decrease, respectively. The agonist-like behavior of LEV200 on the inhibitory M2 mAChR subtype, observed in this work, could contribute to explain the reduction on oxotremorine-induced tremors and the delay on pilocarpine-induced seizures, by an increase in the attenuation of neuronal activity mediated by the M1 receptors. [3H]-spiroperidol binding assays also showed a downregulation of dopaminergic D2 receptors, induced by LEV200 alone treatment. Although this effect was reverted on P400 presence, maybe it posses some influence on LEV200 protective effect, since the stimulation of these receptors can reduce the intensity of pilocarpine induced-seizures. Objectifying to investigate if LEVâ mechanism of action also involves anti-oxidant proprieties, neurochemical analysis were carried out in hippocampus and striatum and showed that P400 produced an increased lipid peroxidation in hippocampus, main epileptogenic focus on cholinergic agents induced-seizures, demonstrating and confirming the involvement of free radical oxygen injury in the P400 induced brain injury. However, LEV200 pretreatment abolished this increase, bringing lipid peroxidation levels back to normal values, suggesting an anti-oxidative property of LEV. Our finds also showed a decrease of nitrite levels and stabilization of catalase activity in hippocampus and striatum, beyond an increase on reduced glutathione levels on hippocampus, induced by LEV200 treatment before P400 administration. In this way, the anti-oxidative action of LEV was showed in several stages involved on oxidative injury, suggesting a novel mechanism of its protector effects.